Functional liver tissue engineering by an adult mouse liver‐derived neuro‐glia antigen 2‐expressing stem/progenitor population. (23rd May 2017) - Zhang, Hongyu; Siegel, Christopher T.; Li, Jing; Lai, Jiejuan; Shuai, Ling; Lai, Xiangdong; Zhang, Yujun; Jiang, Yan; Bie, Ping; Bai, Lianhua
Abstract: Deaths due to end‐stage liver diseases are increasingly registered annually in the world. Liver transplantation is the ultimate treatment for end‐stage liver diseases to date, which has been hampered by a critical shortage of organs. The potential of decellularized liver scaffolds (DLS) derived from solid organs as a three‐dimensional platform has been evolved as a promising approach in liver tissue engineering for translating functional liver organ replacements, but questions still exist regarding the optimal cell population for seeding in DLS and the preparation of the DLS themselves. The aim of our study was to utilize a sodium dodecyl sulfate decellularization procedure in combination with a low concentration of trypsin (0.005%)–ethylenediaminetetraacetic acid (0.002%) process to manufacture DLS from whole mouse livers and recellularized with hepatic stem/progenitors for use in liver tissue engineering and injured liver treatment. Results showed that the DLS generated with all the necessary microstructure and the extracellular components to support seeded hepatic stem/progenitor cell attachment, functional hepatic cell differentiation. Hepatic differentiation from stem/progenitor cells loaded by DLS was more efficient than that of the stem/progenitor cells in the two‐dimensional cell culture model. In summary, the method of DLS loaded by hepatic stem/progenitor cells provided by this study was effective in maintaining DLS extracellular matrix to introduce seeded stem/progenitor cell differentiation, hepatic‐like tissue formation and functional hepatic protein production in vitro that promoted functional recovery and survival in a mouse model of dimethylnitrosamine‐induced liver cirrhosis after auxiliary heterotopic liver transplantation. Copyright © 2016 John Wiley & Sons, Ltd.